The South strikes back - Carter, Hodding (Civil rights in Mississippi., 2022)
"In The South Strikes Back, Hodding Carter III describes the birth of the white Citizens' Council in the Mississippi Delta and its spread throughout the South. Carter begins with a brief historical overview and traces the formation of the Council, its treatment of African Americans, and its impact on white communities, concluding with an analysis of the Council's future in Mississippi. Through economic boycott, social pressure, and political influence, the Citizens' Council was able to subdue its opponents and dominate the communities in which it operated. Carter considers trends working against the Council-the federal government's efforts to improve voting rights for African Americans, economic growth within African American communities, and especially the fact that the Citizens' Council was founded on the defense of segregation's status quo and dedicated to its preservation. As Carter writes in the final chapter, "Defense of the status quo, as history has shown often enough, is an arduous task at best. When, in a democracy such as ours, it involves the repression of a minority, it becomes an impossibility.""--